Economic literacy of 11th grade social science students at SMAN 8 Malang - Islamudin, Mohamad Mujahid; Wafa, Muhammad Ali; Salma, Udsy Silviatus; Bashith, Abdul (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED), 2025)
Education plays a crucial role in shaping students’ character, including their ability to understand economic concepts rationally and apply economic literacy in daily decision-making. However, research on the level of economic literacy among Indonesian high school social science students, especially those assessed using the National Council on Economic Education (NCEE) standards, remains limited. This study aims to fill that gap by analyzing the extent to which 11th-grade social science students at SMAN 8 Malang comprehend basic economic concepts and apply them in rational economic behavior. Using a quantitative descriptive approach, the study involved a population of 210 students, with 138 randomly selected respondents (5% margin of error). Economic literacy was measured using the NCEE-based 20-item economic understanding test. The results show that students’ economic literacy levels fall within the high to very high categories: 49.3% in the high category and 38.6% in the very high category, with an average score of 77.75 (minimum 30, maximum 95). These findings indicate that students demonstrate strong mastery of key concepts such as financial planning, resource management, and responsible economic decision-making. Theoretically, the study contributes to discussions on economic literacy development among adolescents, particularly within the Indonesian social science curriculum context. Practically, the results highlight the need for schools to strengthen applied economic learning strategies to support rational, future-oriented decision-making among students.